CONFORMITY ANALYSIS OF CELL TOPICS IN BIOLOGY TEXTBOOK FOR 11TH GRADERS WITH THE BASIC COMPETENCIES OF CURRICULUM 2013 - Shania Aurora Nachrizanti; Nani Aprilia (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2022)
Textbooks are prepared to help teachers convey material to students in class easily. The textbook must meet the needs of students in its presentation by considering the suitability of the content of the material with the basic competencies to be achieved. This study aims to determine the level of conformity between the cell topics in the biology textbook for class XI and the basic competencies of the curriculum 2013 in terms of the breadth and depth of the material. This research is a quantitative descriptive study by analyzing the biology textbook for class XI from Erlangga and Yudhistira. The data collection technique used is observation using the observation sheet. The data analysis used descriptive quantitative. At the data analysis stage, it was carried out by several reviewers consisting of researchers, colleagues, and high school teachers in a Focus Group Discussion (FGD). The results showed that the suitability of the topic of cell in terms of the breadth of the material in textbooks A and B obtained a percentage of 75%. While the suitability of the content in terms of the depth of the material, the results obtained are 95.83% in textbook A and 83.33% in textbook B. It is because textbook A only fulfills 23 of the total 24 scores. Meanwhile, textbook B only fulfills 20 of the total 24 scores. Based on the study results, it can be concluded that the level of material breadth in textbooks A and B have an appropriate category. On the other hand, the level of material depth in textbook A and textbook B has a very appropriate category.